2010
DOI: 10.1002/hep.23775
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effects of Beta-Blockers on Survival in Patients With Cirrhosis and Refractory Ascites†,‡

Abstract: Beta-blockers may have a negative impact on survival in patients with cirrhosis and refractory ascites. The aim of this study was to evaluate the effect of the administration of betablockers on long-term survival in patients with cirrhosis and refractory ascites. We performed a single-center, observational, case-only, prospective study of patients with cirrhosis and refractory ascites who did or did not receive beta-blockers for the prevention of gastrointestinal bleeding; 151 patients were included. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
394
11
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 483 publications
(431 citation statements)
references
References 328 publications
(407 reference statements)
10
394
11
16
Order By: Relevance
“…For instance, in early cirrhosis, there is only mild splanchnic and systemic hyperdynamic circulatory state, therefore NSBB are weakly active with some increase in their adverse events as it was shown in the large multicenter clinical trial from Groszmann and colleagues [27] . On the other side, several circulatory changes accompany advanced cirrhosis such as peripheral vasodilation, effective hypovolemia, and arterial hypotension [28][29][30][31] , it is at that time when the maintenance of cardiac output and blood pressure becomes paramount in prolonging overall survival, and the hemodynamic effects of beta-blockers become potentially harmful [26,32,33] .…”
Section: Beta-blockers In Cirrhosismentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in early cirrhosis, there is only mild splanchnic and systemic hyperdynamic circulatory state, therefore NSBB are weakly active with some increase in their adverse events as it was shown in the large multicenter clinical trial from Groszmann and colleagues [27] . On the other side, several circulatory changes accompany advanced cirrhosis such as peripheral vasodilation, effective hypovolemia, and arterial hypotension [28][29][30][31] , it is at that time when the maintenance of cardiac output and blood pressure becomes paramount in prolonging overall survival, and the hemodynamic effects of beta-blockers become potentially harmful [26,32,33] .…”
Section: Beta-blockers In Cirrhosismentioning
confidence: 99%
“…After almost three decades of their landmark study in 1981 showing the benefits of NSBB in the prevention of variceal bleeding in patients with cirrhosis [8] , the use of beta-blockers was questioned by Serste et al when they found out that NSBB therapy in patients with refractory ascites was associated with poor survival [32] . In…”
Section: Beta-blockers In Decompensated Cirrhosis and Refractory Ascitesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] The restriction of infectious outcomes to those with hospitalisation results in excluding out-patient infections. However, it can be argued that out-patient episodes would be poorly captured from a coding perspective and have a milder effect on overall prognosis than infections associated with hospitalisation.…”
mentioning
confidence: 99%
“…1,2 We agree with the authors that the evidence is split regarding the effects of NSBB on infections and given the poor prognosis of these infections, efforts to improve outcomes are critical. [3][4][5] The restriction of infectious outcomes to those with hospitalisation results in excluding out-patient infections. However, it can be argued that out-patient episodes would be poorly captured from a coding perspective and have a milder effect on overall prognosis than infections associated with hospitalisation.…”
mentioning
confidence: 99%